2020
DOI: 10.1186/s13020-020-00306-0
|View full text |Cite
|
Sign up to set email alerts
|

Jowiseungki decoction affects diabetic nephropathy in mice through renal injury inhibition as evidenced by network pharmacology and gut microbiota analyses

Abstract: Background: Jowiseungki decoction (JSD) is a prescription commonly used for the treatment of diabetic complications or diabetic nephropathy (DN) in traditional medicine clinics. However, the underlying therapeutic mechanisms of JSD are still unclear. Methods: Streptozotocin (STZ)-induced DN mice were administered 100 and 500 mg/kg JSD for 4 weeks, and the therapeutic mechanisms and targets of JSD were analyzed by network pharmacology and gut microbiota analyses. Results: JSD significantly decreased the increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 41 publications
2
8
0
Order By: Relevance
“…Meanwhile, network pharmacology can provide insights into the molecular mechanisms of herbal prescriptions at the molecular and systematic levels (Zhang et al, 2017c). Recently, some researchers have successfully used the integrated network pharmacology and gut microbiota analysis strategy to explore the interactions between organisms and TCM prescriptions, bringing great inspiration to the mechanism research of FLZP (Gao et al, 2018;Meng et al, 2020). In this study, network pharmacology and gut microbiota analysis were applied to explore the effects of FLZP regulating gut microbiota of IBS-D, which could provide a basis for the clinical application of FLZP treating IBS-D. Commission, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, network pharmacology can provide insights into the molecular mechanisms of herbal prescriptions at the molecular and systematic levels (Zhang et al, 2017c). Recently, some researchers have successfully used the integrated network pharmacology and gut microbiota analysis strategy to explore the interactions between organisms and TCM prescriptions, bringing great inspiration to the mechanism research of FLZP (Gao et al, 2018;Meng et al, 2020). In this study, network pharmacology and gut microbiota analysis were applied to explore the effects of FLZP regulating gut microbiota of IBS-D, which could provide a basis for the clinical application of FLZP treating IBS-D. Commission, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…It decreases renal inflammation and fibrosis by regulating nuclear factor-κB/α-SMA and protein kinase C-alpha/phosphatidylinositol-3-kinase/protein kinase B signaling pathways. In addition, JSD has an impact on modifying the intestinal bacterial composition [163]. In another study conducted by Zhao and his colleagues, they concluded that Tangshen Formula, a Chinese herbal medicine, modulates the GM and decreases renal inflammation.…”
Section: Main Focus Salient Findings Country Year and Reference Physi...mentioning
confidence: 99%
“…BHID is composed of Gypsumfibrosum, Anemarrhena asphodeloides Bunge, Panax ginseng C.A.Mey., Glycyrrhiza glabra L. and Oryzasativa L. seeds. Meng et al (2020) utilized metabolomics combined with intestinal flora analysis to attempt to explain the mechanism of BHID in the treatment of DKD. They found that after oral administration of BHID (0.5 g/kg/d), there was a significant difference in the abundance of Actinobacteria phylum between the BHID-treated group and control groups.…”
Section: Herbal Medicine Gut-kidney Axis and Dkd/ckdmentioning
confidence: 99%